Tingkat Adopsi Petani Terhadap Pengembangan Jagung Manis (Kasus di Subak Padanggalak, Kecamatan Denpasar Timur) - David Tagu Todu; Nyoman Yudiarini; Luh Putu Kirana Pratiwi (AGRIMETA : Jurnal Pertanian Berbasis Keseimbangan Ekosistem, 2020)
This study discusses the level of farmer adoption in corn development in Subak Padanggalak, Kesiman Kertalangu village, East Denpasar District, Denpasar City Regency. This study aims to: (1) determine the the level of farmer adoption in corn development (2) determine the factors that affect the level of farmer adoption in corn development. Respondents used 25 saturated sampling methods. The first objectiveanalysis used the secod objective analysis used regression test (t) and test (f) methods. The results of this study indicate that the level of farmers has a positive effect. The factors that influence the level of farmer adoption, namely age, eduction, land area, land status, farming experience, and number of family members have a positive effect on the level of farmer adoption for corn development